IMPLEMENTASI KEBIJAKAN DIVERSIFIKASI KONSUMSI PANGAN LOKAL DI KABUPATEN PATI - Utami, Sri (Jurnal Litbang: Media Informasi Penelitian, Pengembangan dan IPTEK, 2018)
ENGLISHThe pattern of community food consumption in Pati Regency has not been ideal yet in practice. The aims of this study is to find out the policy implementation of local food consumption diversification in Pati Regency, and to analyze the factors that influence the implementation of the policy. This research used qualitative method. The research was conducted in Pati regency, by conducting in-depth interviews to 18 (eighteen) informants from related agencies and targetted groups/communities. The data analyses include data reduction, data presentation and conclusion. The results of the research showed that the policy implementation of diversification of local food consumption in Pati Regency did not run well. There were 4 factors that impeded the policy implementation: (1) Communications, the delivery of policy content/socialization to policy implementers has not conducted well; (2) Resources, inadequate human resource in terms of quantity and quality. The agencies actively involved were only 7 (seven) of 11 (eleven) related agencies; (3) Organizational structure, the preparation of SOP was too late so it did not support effectively the implementation the policy; and (4) Communities attitudes towards local food, the communities considered that local food was